2015
DOI: 10.1111/ppe.12204
|View full text |Cite
|
Sign up to set email alerts
|

A Case‐Crossover Study of Temperature and Infant Mortality in California

Abstract: This study suggests that infants are a vulnerable subgroup to heat exposure. Further studies should be conducted with a sufficient number of cases of infant deaths in other locales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…Lastly, two studies examining immediate neonatal impacts due to ambient temperature exposure were included in this review. Both demonstrated that heat waves increase stress in neonates, either as a function of heat-related neonatal intensive care unit (NICU) admissions [ 44 ], or through heat-related infant death [ 45 ]. Kakkad et al [ 44 ] specifically explored NICU admissions on extreme heat days in Ahmedabad, India, where most births occur outside of hospitals and extreme heat is considered to be an excess of 42 °C; heat waves resulted in an increase of admissions.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, two studies examining immediate neonatal impacts due to ambient temperature exposure were included in this review. Both demonstrated that heat waves increase stress in neonates, either as a function of heat-related neonatal intensive care unit (NICU) admissions [ 44 ], or through heat-related infant death [ 45 ]. Kakkad et al [ 44 ] specifically explored NICU admissions on extreme heat days in Ahmedabad, India, where most births occur outside of hospitals and extreme heat is considered to be an excess of 42 °C; heat waves resulted in an increase of admissions.…”
Section: Resultsmentioning
confidence: 99%
“…Ülkemizde sağlık çalışanlarına yapılan bir araştırmada riskli olmasına rağmen bebekler uyurken yastık kullanılabileceğini söyleyen pediatri hemşirelerin oranı %32, çocuk doktorlarının ise %23,8 olarak belirtilmiştir (25). Bebeğin yaşam/uyuma ortamının aşırı sıcak ya da soğuk olması bebekleri olumsuz etkilemekte hatta ölümlerine sebep olmaktadır (26). Ayrıca literatürde bebeklerin yorganlarının ayak uçlarının yatağın altına sıkıştırılmaması da ani bebek ölüm sendromu açısından risk faktörü olarak tanımlanmaktadır (27).…”
Section: Veri Toplamaunclassified
“…The case–crossover design is ideal for assessing associations between short-term exposures and rare outcomes such as SIDS, 26 and has been used in previous studies assessing heat exposure and SIDS. 19,22 The case–crossover design compares each subject's exposure in a time period just prior to a case-defining event with that subject's exposure at other times. Since each subject is his or her own control, all measured or unmeasured time-invariant subject characteristics (e.g., sex, race, socioeconomic status, year/season of birth) are inherently adjusted for, such that there is no confounding by these characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…28 We assessed the effect of AC on temperature-related SIDS risk by stratifying the analysis by level of air conditioning prevalence (i.e., lower, middle, and upper tertiles). Lastly, as apparent temperature has been used in previous studies examining temperature-related mortality, 22,29 we compared the risk estimates derived from apparent temperature and air temperature. Apparent temperature is defined as an individual's perceived air temperature at a given humidity level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation